Modelling factors encouraging knowledge sharing culture as a socio-innovation in collaborative era / Suwito Eko Pramono ... [et al.] - Pramono, Suwito Eko; Sari Melati, Inaya; Wijaya, Atika; Sahudin, Zahariah; Abdullah, Hasni (Universiti Teknologi MARA, 2022)
This study aims to confirm how fit measured indicators of a designed instrument describing knowledge sharing behaviour among faculty members of Higher Education Institution (HEI) to stimulate higher collaboration works supporting Independent Learning, Freedom Campus (Merdeka Belajar Kampus Merdeka-MBKM) program in Indonesia. Some independent variables were proposed in this study, including personal forces (autonomy, normative beliefs on knowledge sharing, leadership, and attitude toward knowledge sharing); as well as institutional forces (expected rewards and associations, expected contribution, structure, technology platform, affiliation to institution, and affiliation to discipline). As many as 264 Indonesian faculty members participated in this study using anonymous google form. Using Confirmatory Factor Analysis (CFA), this study established the reliable constructs for both personal and institutional forces. There were two phases for defining the best items for the instrument, hence the modified items excluded 12 items from the original ones to form a more fit model at the modification stage. The policy makers can use this model to identify the knowledge sharing intention among faculty members in order to design appropriate interventions.